Critical Choice in "Documenting" Practice as Research - Hunter, Lynette (Performance Matters, 2023)
Documenting practice as research is a graphic attempt to carry the materiality of practice to an audience, while articulating focuses on communicating the practice in language generic to academic research. The former holds a promise of opening the field to what has not been discursively recognized, by sociosituated people presencing unseen, unheard, obscured, erased ways of living and valuing. The latter is already on sociocultural ground. Which one we use is a critical choice: to articulate to a wider audience, or to engage through documenting with a usually much smaller group of people who will collaborate on being with a not-known materiality.